Activating collective co-production of public services: influencing citizens to participate in complex governance mechanisms in the UK - Bovaird, Tony et al (2016)
Previous research has suggested that citizen co-production of public services is more likely when the actions involved are easy and can be carried out individually rather than in groups. This article explores whether this holds in local areas of England and Wales. It asks which people are most likely to engage in individual and collective co-production and how people can be influenced to extend their co-production efforts by participating in more collective activities. Data were collected in five areas, using citizen panels organized by local authorities. The findings demonstrate that individual and collective co-production have rather different characteristics and correlates and highlight the importance of distinguishing between them for policy purposes. In particular, collective co-production is likely to be high in relation to any given issue when citizens have a strong sense that people can make a difference ('political self-efficacy'). 'Nudges' to encourage increased co-production had only a weak effect. - Reproduced.
Keywords: Public administration